Range formula based on angle of dispersion and nozzle configuration from an impact sprinkler - Jiang, Yue; Issaka, Zakaria; Li, Hong; Tang, Pan; Chen, Chao (International Journal of Agricultural and Biological Engineering, 2019)
Jet breakup and dispersion from impact sprinkler are mainly influenced by the configurations of nozzle and dispersion device. Based on the structure, different types of nozzles were designed and tested with a pointed tip dispersion device under low pressure conditions. Experiments were performed using High-Speed Photographic technique, and Matlab computation program was established and applied to determine the initial jet breakup length and angle of dispersion from the nozzles. The sprinkler range decreased with the increase in diameter of nozzle, and the largest range of 15.1 m was produced from sprinkler with 6 mm nozzle size under a pressure of 150 kPa. The angle of dispersion decreased with the increase of jet velocity, the spray coverage from sprinkler with 6 mm nozzle size was 1478 mm under 150 kPa, and was not statistically different when the pressure was increased. A new range formula was established for sprinkler with dispersion device through curve fitting of the parameters of initial jet breakup length, angle of dispersion, nozzle size and working pressure. The new formula was reliable for calculating range with a relative error less than 3%. Since the formula is based on the angle of dispersion, it could be useful to estimate uniformity of water distribution in sprinkler irrigated fields.Keywords: fixed dispersion device, range, jet breakup, angle of dispersion, spray coverage, impact sprinklerDOI: 10.25165/j.ijabe.20191205.4646Citation: Jiang Y, Issaka Z, Li H, Tang P, Chen C. Range formula based on angle of dispersion and nozzle configuration from an impact sprinkler. Int J Agric & Biol Eng, 2019; 12(5): 97–105.